The efect of carbon coating on the arsenite sorption by magnetic carbon nanocomposites - Burbano Patiño, Aura Alejandra (2024)
Arsenic pollution has emerged through anthropogenic activities and natural mineral leaching processes. This study aims to advance the use of magnetic carbon nanocomposites (MCNs) in the sorption of arsenic, studying the infuence of feedstock and the presence of carbon coating on magnetic nanoparticles. Previous works have shown that post-pyrolysis treatment improves the stability of MCNs by reducing iron leaching due to the formation of a carbon coating that encapsulates the iron oxide nanoparticles. However, this carbon coating could infuence the adsorption properties of MCNs. This investigation deals with arsenic adsorption by four MCNs prepared by co-precipitation of magnetite (Fe3O4) nanoparticle into four carbonaceous matrixes, followed by a post-pyrolysis treatment. The pristine carbonaceous matrixes used in the present work were commercial activated carbon (CAC), charcoal (CC), hydrochar from the orange residue (HCOR), and biochar from sunfower husk (BCSFH). Pristine carbonaceous materials and MCNs without post-pyrolyzed were also used as arsenic sorbents in water solutions. Additionally, kinetic studies were carried out to explore the sorption properties of diferent MCNs and pristine materials, concerning the removal efciencies (expressed as a percentage) and adsorption capacities, determining the equilibrium time. The results demonstrated that the presence of magnetite increases the adsorption of arsenic, being higher in the case of materials obtained by direct co-precipitation than in materials subjected to a post-pyrolysis process. The presence of a carbon layerprotecting the magnetite slightly decreases the adsorption of arsenic.